92. Myogenic vestibular-evoked potentials: An extension of the assessment protocol. Issue 12 (December 2017) - Lullo, F.; Piscosquito,; Provitera, V.; Zamprotta, L.; Prisco, C.; Lanzillo, B.; Manganelli, F.; Santoro, L.; Nolano, M.
Abstract : Vestibular-Evoked-Myogenic-Potentials (VEMPs) represent a muscular response following an intense acoustic stimulation. The cVEMPs explore a reflex arc (from saccule to the neck musculature) and usually are only recorded from sternocleidomastoideus (SCM). 1 They are non-invasive, well-tolerated, simple-to-perform and very useful in several diseases. The normal response is a biphasic complex P13/N23. We propose a more extensive protocol. We recruited 31 subjects (mean age ± SD:50.8 ± 19.0). VEMPs were recorded symmetrically and simultaneously through surface electromyography from SCM, splenius (SPL), trapezius (TRP) and orbicularis oculi (OO). The sensitivity was 20  μ V, band pass filter 20–2000 Hz, tone acoustic stimulus was monaural and binaural at 500 Hz, rate at 5.3 Hz. Three runs of 150 sweeps were averaged. The patients remained in clinostatic position with anterior neck flexion. Like the SCM cVEMP, the SPL and TRP cVEMP was characterized by a biphasic wave of muscle activity that began at ∼13 ms. Responses were consistent and repeatable. VEMPs latencies and amplitude showed a higher inter-reliability for the four muscles. The protocol offer a complementary target for cVEMP assessments. The simultaneous recording of oVEMPs and cVEMPs provide the evaluation of the ascending and descending vestibular pathways, allowing an extensive overview of brainstem function.